Periostin Is Expressed by Pericytes and Is Crucial for Angiogenesis in Glioma. Issue 8 (10th July 2020) - Huizer, Karin; Zhu, Changbin; Chirifi, Ihsan; Krist, Bart; Zorgman, Denise; van der Weiden, Marcel; van den Bosch, Thierry P P; Dumas, Jasper; Cheng, Caroline; Kros, Johan M; Mustafa, Dana A
Abstract: The expression of the matricellular protein periostin has been associated with glioma progression. In previous work we found an association of periostin with glioma angiogenesis. Here, we screen gliomas for POSTN expression and identify the cells that express periostin in human gliomas. In addition, we study the role of periostin in an in vitro model for angiogenesis. The expression of periostin was investigated by RT-PCR and by immunohistochemistry. In addition, we used double labeling and in situ RNA techniques to identify the expressing cells. To investigate the function of periostin, we silenced POSTN in a 3D in vitro angiogenesis model. Periostin expression was elevated in pilocytic astrocytoma and glioblastoma, but not in grade II/III astrocytomas and oligodendrogliomas. The expression of periostin colocalized with PDGFRβ + cells, but not with OLIG2 + /SOX2 + glioma stem cells. Silencing of periostin in pericytes in coculture experiments resulted in attenuation of the numbers and the length of the vessels formation and in a decrease in endothelial junction formation. We conclude that pericytes are the main source of periostin in human gliomas and that periostin plays an essential role in the growth and branching of blood vessels. Therefore, periostin should be explored as a novel target for developing anti-angiogenic therapy for glioma.